Analysis for Difficulty during Freeze-Drying Feizixiao Lychees. (24th December 2017) - Huang, L. L.; Qiao, F.; Peng, G.; Fang, C. F.
Abstract : Compared to other cultivar lychees, volume density of Feizixiao lychee was higher due to serious shrinkage during freeze-drying (FD). Guiwei lychee and Nuomici lychee were used for comparison in order to illuminate the reason of the aforementioned phenomenon. Lower prefreezing temperature could not improve the volume density of Feizixiao lychee. Microstructure results show that pulp cell of Feizixiao lychee (tail) was smaller and more compact than Guiwei and Nuomici lychee pulp cell. In addition, there is a membrane around the surface of Feizixiao lychee pulp. And the microstructure of Feizixiao lychee tip pulp cell is different from tail pulp cell. Membrane and tip pulp cell are both smaller and more compact than tail pulp cell. These structure differences hinder the moisture removing of Feizixiao lychee during FD. Removing the membrane and tip pulp could not improve the volume density of Feizixiao lychee. Ultrasound treatment for 30 min could significantly enhance the volume density of Feizixiao lychee.